Investigation of ternary blended binder PVA fibre reinforced cementitious composites as repair material / Loh Zhi Pin - Loh , Zhi Pin (2019)
Fibre reinforced cementitious composites (FRCC) is a type of high-performance concrete with unique features suitable for repair application. To develop a well-performed FRCC, good fibre dispersion is crucial and it is achievable via high binder content without compromising the mechanical properties. Therefore, supplementary cementitious material is used to reduce the heat of hydration as well as improving the workability of FRCC. In this research, the focus was on using fixed water-to-binder ratio to study the effect of different binder (900 kg/m3, 1100 kg/m3 and 1300kg/m3) and ground granulated blast furnace slag (GGBS) (0, 30 % and 60 % as fly ash replacement) content on the performance of FRCC as repairing material. Overall, the research was planned into two phases. The initial phase served as a preliminary stage in selecting the FRCC by fulfilling the minimum requirement in terms of workability and compressive strength; whereas the final phase was the testing of mechanical properties, namely, splitting tensile, flexural, slant shear and impact strength tests. The results showed that workability and rheology of FRCC can be improved with higher binder content or using 30 % GGBS replacement. Conversely, FRCC with lower binder content and higher GGBS content induced higher compressive strength. Ultimately, six mixtures of FRCC were selected in the final phase by fulfilling the minimum requirement in terms of workability and compressive strength. Based on the experimental results, the effect of GGBS was observed to be varied at different binder contents on the mentioned mechanical properties and ductility of FRCC; as this is primarily attributed to the interfacial bond of matrix-fibre and matrix strength. Based on the performance and the economic considerations, binder content at 1100kg/m3 and 30% GGBS replacement in FRCC was the most optimum. In overall, the usage of GGBS as partial replacement for fly ash showed positive effect in developing FRCC for repair work as the minimum requirement for mechanical properties of repair material could be fulfilled.